A comparison of Bayesian hierarchical modeling with group‐based exposure assessment in occupational epidemiology. (3rd April 2013) - Xing, Li; Burstyn, Igor; Richardson, David B.; Gustafson, Paul
Abstract : We build a Bayesian hierarchical model for relating disease to a potentially harmful exposure, by using data from studies in occupational epidemiology, and compare our method with the traditional group‐based exposure assessment method through simulation studies, a real data application, and theoretical calculation. We focus on cohort studies where a logistic disease model is appropriate and where group means can be treated as fixed effects. The results show a variety of advantages of the fully Bayesian approach and provide recommendations on situations where the traditional group‐based exposure assessment method may not be suitable to use. Copyright © 2013 John Wiley & Sons, Ltd.